Relative economic benefits of tactical anthelmintic treatment and urea-molasses block supplementation of Boer goats raised under extensive grazing conditions at Onderstepoort, Pretoria, South Africa - A.F. Vatta; R.C. Krecek; R.A. Pearson; M.F. Smith; M.O. Stenson; E.F. Van Wijk; L.J.S. Harrison (Onderstepoort Journal of Veterinary Research, 2008)
The potential economic benefits of combining tactical anthelmintic treatment for gastrointestinal nematodes and nutritional supplementation with urea-molasses blocks were examined in Boer goats raised under extensive grazing conditions in the summer rainfall area of South Africa. Eight groups of nine goats were monitored over a 12-month period from 1 October 2002 to 9 October 2003. Ad libitum nutritional supplementation with urea-molasses blocks was provided when the goats were housed at night, during the summer (wet season -December 2002 to February 2003), and / or the winter (dry season -June 2003 to August 2003). All the goats were treated symptomatically for Haemonchus contortus infection when deemed necessary by clinical examination of the conjunctiva for anaemia using the FAMACHA© system. Half the groups were tactically treated for gastrointestinal nematodes in mid-summer (28 January 2003). Under the symptomatic treatment, climatic and extensive grazing conditions encountered during the trial, feed supplementation in the winter dry season had the greatest economic benefit and is therefore recommended. Tactical anthelmintic treatment afforded no additional advantage, but the nematode challenge was lo